Quantitative and qualitative characterization of Two PD-L1 clones: SP263 and E1L3N. Issue 1 (December 2016) - Smith, Jacquelyn; Robida, Mark; Acosta, Krista; Vennapusa, Bharathi; Mistry, Amita; Martin, Greg; Yates, Alton; Hnatyszyn, H.
Abstract Background Programmed Death Ligand 1 (PD-L1) is an immune modulating protein expressed on the surface of various inflammatory cells, including T Cells, B Cells, dendritic cells, and macrophages. PD-L1 represents an important diagnostic target; expression of PD-L1 on the surface of tumor cells, or within tumor-associated immune cells, is an important predictor of likely response to targeted therapies. In this study, we describe the optimization of immunohistochemistry (IHC) assays using two PD-L1 antibodies (SP263 and E1L3N) and compare the performance of the optimized assays. Methods Fully automated immunohistochemical assays were optimized for the VENTANA PD-L1 (SP263) Rabbit Monoclonal Antibody and the PD-L1 (E1L3N®) XP® Rabbit mAb using instruments and detection chemistries from Ventana Medical Systems, Inc. ("SP263 assay" and "E1L3N assay, " respectively). Tissue microarrays (TMAs) containing formalin fixed paraffin embedded (FFPE) non-small cell lung cancer (NSCLC) cases were used for the optimization and comparison staining. H scores were used for membrane scoring whereas percent positivity was used for tumor-associated immune cell scoring. Results One-hundred NSCLC TMA case cores each stained with the SP263 and E1L3N assays were evaluated by two pathologists in a blinded study. Analysis of these specimens showed that the SP263 assay was more sensitive and had a wider dynamic range than the E1L3N assay. For sensitivity, many cases were found to be negative for membrane staining with the E1L3N assay, but had measurable staining with the SP263 assay. Dynamic range was demonstrated by the SP263 assay having well-distributed H scores while the E1L3N assay had a significantly higher proportion of cases clustered in the lowest H score bins. For tumor-associated immune cell staining, the two assays identified similar amounts of cells staining in each case, but the SP263 assay gave overall darker staining. Conclusion Since PD-L1 status is important for targeted therapies, having a specific and accurate diagnostic test is crucial for identifying patients who could benefit from these treatments. Due to its staining intensity, scoring range, and pathologist preference, the SP263 IHC assay has been deemed superior to the E1L3N IHC assay. Future clinical utility remains to be determined.